Clinical and neuropsychological characterization of SuperAgers residing in Delhi and National Capital Region of India—A cross‐sectional study - Ritika Batra; Deepa Anil Kumar; Abhijith Rao; Gauri Shanker Kaloiya; Maroof Ahmad Khan; Sujata Satapathy; Avinash Chakrawarty; Nidhi Soni; Pramod Kumar; Prasun Chatterjee (Aging Medicine, 2024)
Abstract Introduction SuperAgers (SA) are older adults who exhibit cognitive capacities comparable to individuals who are three or more decades younger than them. The current study aimed to identify the characteristics of Indian SA by categorizing 55 older adults into SA and Typical Older Adults (TOA) and comparing their performance with a group of 50 younger participants (YP) (aged 25–50). Methods A total of 105 participants were recruited after obtaining informed written consent. The cognitive abilities of the participants were assessed using Wechsler Adult Intelligence Scale (WAIS)‐IVINDIA, Color Trails Test, Boston Naming Test (BNT), and Rey Auditory Verbal Learning Test. Results SA outperformed TOA in all cognitive assessments (P < 0.001) and surpassed YP in BNT and WAIS‐IV. SA's delayed recall scores were notably higher (12.29 ± 1.51) than TOA (6.32 ± 1.44). Conclusion SA excelled in all cognitive domains demonstrating resilience to age‐related cognitive decline. This study highlights Indian SuperAgers' exceptional cognitive prowess.